Soil carbon pools in two natural grasslands of Serbian highlands - Saljnikov Elmira; Lukić Sara; Miljković Predrag; Koković Nikola; Perović Veljko; Čakmak Dragan; Belanović-Simić Snežana (Glasnik Šumarskog Fakulteta: Univerzitet u Beogradu, 2019)
Grasslands are a major player in the global carbon cycle, although carbon stocks in grasslands are influenced by human activities and natural disturbances. The aim of this study is to determine differences in carbon stock on two test areas of grassland ecosystem in the highlands of Stara Planina and Zlatar Mountains (Serbia). The investigated sites are natural mountain grasslands of the same vegetation community (Agrostietum capillarisPavl. 1955) and soil type (Umbric Leptosol (Dystric) and Haplic Cambisol (Dystric)), but with different grazing intensity. Aboveground and belowground biomasses were measured in each sample plot, and soil was sampled at fixed depths of 0-10, 10-20 and 20-40 cm. The estimation of C stock and the rate of soil C accumulation were determined by the Tier 2 method IPCC (2003). Carbon mineralization potentials were determined via sequential incubation procedure in the laboratory conditions. According to the obtained results, the greater amount of precipitation on Mt. Stara Planina resulted in a greater accumulation of aboveground biomass, which was subjected to a greater decomposition in situ, thus showing a lower amount of PMC in vitro. In addition, potentially mineralizable carbon (PMC) among the sample plots from both sites indicates that the mineralization of soil organic matter was more influenced by the factors related to the soil characteristics, climatic conditions and grazing. [Project of the Serbian Ministry of Education, Science and Technological Development, Grant no. 043007: The Climate Change and Its Impact on the Environment - Monitoring, Adaptation and Mitigation]